A carboxymethyl chitosan composite material for joint cavity and preparation method thereof

By selecting raw materials with good biocompatible properties and performing functional modification treatment, a carboxymethyl chitin composite material for joint cavity was prepared, which solved the problems of low elastic modulus, large swelling rate, and low cell survival rate in the prior art, and achieved the effect of improving elastic modulus, reducing swelling rate and ensuring cell survival rate.

CN119564949BActive Publication Date: 2025-04-08YANTAI WANLI MEDICAL EQUIP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510143837.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-08
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

The current problems of the composite material for articular cavity have low elastic modulus, large swelling rate, and low cell survival rate, which seriously affect its actual use.

Method used

By selecting carboxymethyl chitin, hyaluronic acid, sodium alginate and chitosan with good biocompatible properties as raw materials and performing functional modification treatments, a carboxymethyl chitin composite material for joint cavity was prepared. Through the synergistic action of each component, the elastic modulus of the composite material is improved, the swelling rate is reduced, and the good cell survival rate is ensured.

Benefits of technology

It significantly improves the elastic modulus of the composite material, reduces the swelling rate, and ensures good cell survival. At the same time, the composite material also has suitable viscosity and degradation properties, which can meet application needs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of biomedical materials, and specifically relates to a carboxymethyl chitosan composite material for joint cavity and a preparation method thereof. The present invention selects carboxymethyl chitosan, hyaluronic acid, sodium alginate and chitosan with good biocompatibility as raw materials, and performs functional modification treatment respectively to prepare a carboxymethyl chitosan composite material for joint cavity. Through the synergistic effect of each component, the elastic modulus of the composite material is effectively improved, the swelling rate is reduced, and a good cell survival rate is ensured. At the same time, the composite material also has suitable viscosity and degradation performance, which can meet application requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a carboxymethyl chitosan composite material for joint cavity and a preparation method thereof. Background Art

[0002] The joint is composed of the articular surface, the joint cavity, and the joint capsule. There is a small amount of synovial fluid in the joint cavity, which can lubricate the joint. Hydrogel is a material composed of hydrophilic polymer chains, which are connected together by cross-linking to form a solid three-dimensional network. As a new type of material, hydrogel is widely used in biology, medicine and other fields. It is favored for its good biocompatibility and excellent mechanical properties. The use of hydrogel in joint cavity treatment is expected to make up for the shortcomings of the current joint cavity treatment therapies, such as the short drug action time and the difficulty in cartilage tissue regeneration.

[0003] A Chinese patent (publication number CN115671405B) discloses a gel for joint cavity injection and its preparation method. The invention obtains gel by mixing polyethylene glycol active ester with cross-linked carboxymethyl chitosan to undergo cross-linking reaction. The gel is crushed and mixed with non-cross-linked carboxymethyl chitosan solution, sterilized, and cooled to obtain joint cavity injection gel. The joint cavity injection gel obtained by this method has better flexibility, no granularity, small friction coefficient, better lubrication performance, good thermal stability, and better safety performance. In addition, polyethylene glycol active ester is used as a cross-linking agent, which has a fast reaction speed and a short time required. At the same time, polyethylene glycol forms reversible hydrogen bonds between carboxymethyl chitosan and polyol molecules, thereby enhancing the stability of the carboxymethyl chitin molecular structure. However, the patent does not solve the problems of low elastic modulus, large swelling rate, and low cell survival rate in the composite materials for joint cavity in the prior art, which seriously affects its actual use.

[0004] Therefore, how to select raw materials with good biocompatibility and perform functional modification to prepare carboxymethyl chitin composite materials for joint cavities, increase the elastic modulus, reduce the swelling rate, and ensure good cell survival rate has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a carboxymethyl chitosan composite material for joint cavity and a preparation method thereof, aiming to solve the problems of low elastic modulus, large swelling rate, low cell survival rate and the like of the composite material for joint cavity in the prior art.

[0006] The present invention selects carboxymethyl chitosan, hyaluronic acid, sodium alginate and chitosan with good biocompatibility as raw materials, and performs functional modification treatment on them respectively to prepare a carboxymethyl chitosan composite material for joint cavity. Through the synergistic effect of each component, the elastic modulus of the composite material is effectively improved, the swelling rate is reduced, and a good cell survival rate is guaranteed.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0008] The first aspect of the present invention provides a method for preparing a carboxymethyl chitosan composite material for a joint cavity, comprising the following steps:

[0009] Step S1: adding 6 to 10 parts of carboxymethyl chitosan and 4 to 6 parts of calcium salt to 100 to 120 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L and mixing them uniformly to obtain a carboxymethyl chitosan solution; adding 20 to 30 parts of polyethylene glycol to 100 to 120 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L and stirring them uniformly to obtain a polyethylene glycol solution; mixing 10 to 20 parts of the carboxymethyl chitosan solution and 80 to 100 parts of the polyethylene glycol solution to perform a curing reaction, filtering, washing with water, and freeze-drying to obtain modified carboxymethyl chitosan;

[0010] Step S2: adding 20 to 30 parts of the modified carboxymethyl chitosan to 100 to 120 parts of a sodium hydroxide solution with a molar concentration of 0.2 mol / L to form a liquid A, and adding 4 to 8 parts of chitosan to 40 to 50 parts of an acetic acid solution with a molar concentration of 0.2 mol / L to form a liquid B;

[0011] Step S3: 100-120 parts of the liquid A and 40-50 parts of the liquid B are mixed, and then 6-10 parts of hyaluronic acid and 1-3 parts of sodium alginate are added and stirred evenly to obtain a carboxymethyl chitosan composite material for the joint cavity.

[0012] As a preferred technical solution of the present invention, the calcium salt is calcium chloride and calcium bicarbonate; the mass ratio of the calcium chloride to calcium bicarbonate is (1~2):1.

[0013] Modified carboxymethyl chitosan introduces polyethylene glycol, which can form intermolecular forces such as hydrogen bonds with carboxymethyl chitosan. The interaction helps to build a more stable and dense structure, thereby significantly improving the mechanical properties of the composite material. At the same time, polyethylene glycol can serve as a physical cross-linking point to improve resilience and durability through cross-linking, making it more resistant to external pressure and deformation. The combined effect improves the elastic modulus.

[0014] As a preferred technical solution of the present invention, the conditions of the curing reaction include: first stirring at 0-4°C for 10-20 minutes, and then reacting at 50-60°C for 10-20 minutes.

[0015] As a preferred technical solution of the present invention, the hyaluronic acid is modified hyaluronic acid; the preparation method of the modified hyaluronic acid comprises: adding 6 to 10 parts of hyaluronic acid to 80 to 100 parts of deionized water by weight, mixing evenly, adjusting the pH to 8.4 to 8.8, then adding 2 to 4 parts of 2-octenylsuccinic anhydride, stirring overnight, dialyzing, and freeze-drying to obtain modified hyaluronic acid.

[0016] As a preferred technical solution of the present invention, the molecular weight of the hyaluronic acid is 50,000 to 250,000.

[0017] Modified hyaluronic acid uses octenyl succinic anhydride as a hydrophobic small molecule to modify the structure of hyaluronic acid. Octenyl succinic anhydride can form a hydrophobic region through the octenyl side chain, reducing the affinity to water molecules, thereby effectively reducing the swelling rate of the composite material; at the same time, the modification of octenyl succinic anhydride can change the surface charge distribution of hyaluronic acid, affect its interaction with cell surface receptors, and reduce the cytotoxicity of the material.

[0018] As a preferred technical solution of the present invention, the sodium alginate is agarose-modified sodium alginate; the preparation method of the agarose-modified sodium alginate comprises: adding 4 to 8 parts of agarose to 100 to 120 parts of deionized water by weight, stirring evenly at 80 to 90° C., cooling to 65 to 75° C., adding 4 to 8 parts of sodium alginate and stirring for 4 to 6 hours to obtain a mixed solution; electrostatically spraying the mixed solution, freeze-drying, and obtaining agarose-modified sodium alginate.

[0019] As a preferred technical solution of the present invention, the conditions of the electrostatic spray include: a liquid flow rate of 1.2-1.8 mL / h, a voltage of 14-18 kV, a receiving distance of 16-20 cm, and a time of 60-80 min.

[0020] Agarose in agarose-modified sodium alginate has good elasticity and strength, while sodium alginate has excellent flexibility. By compounding the two, the material has both good elasticity and flexibility, thereby optimizing the overall mechanical properties of carboxymethyl chitin composite materials for joint cavities and improving the elastic modulus. At the same time, agarose-sodium alginate will form a large number of mutually entangled filamentous structures and irregular depressions, which can better adhere to cells through the rough surface and filamentous tissue, which is beneficial to cell growth and proliferation and improves cell survival rate.

[0021] As a preferred technical solution of the present invention, the chitosan is titanium dioxide-doped chitosan; the preparation method of the titanium dioxide-doped chitosan comprises: in parts by weight, 180-200 parts of deionized water and 70-100 parts of acetic acid are evenly mixed, then 2-4 parts of chitosan are added to fully dissolve, and then 1-3 parts of titanium dioxide are added to ultrasonically disperse for 20-30 minutes and then stirred to react, after the stirring reaction is completed, 80-100 parts of sodium hydroxide solution with a molar concentration of 1 mol / L is added, cooled to room temperature, filtered, washed with water, and dried to obtain titanium dioxide-doped chitosan.

[0022] As a preferred technical solution of the present invention, the stirring reaction conditions include: a stirring speed of 100-200 r / min, a temperature of 40-50° C., and a time of 3-5 h.

[0023] Chitosan in titanium dioxide-doped chitosan is a natural polysaccharide with good biocompatibility and degradability, and can support cell attachment, growth and differentiation; titanium dioxide has certain antioxidant properties, which can reduce the damage of oxidative stress to cells and is beneficial to maintaining the health of cells. The combination of the two can further optimize the surface properties of the material, increase its friendliness to cells, and improve the cell survival rate of the composite material.

[0024] The second aspect of the present invention provides a carboxymethyl chitosan composite material for joint cavity prepared by the method described in the first aspect.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The agarose-modified sodium alginate of the present invention can not only undergo ionic crosslinking with the calcium ions contained in the modified carboxymethyl chitin, but also interact with the protonated amine ions on the titanium dioxide-doped chitosan through the carboxylate to form a first interconnected network. At the same time, after the modified hyaluronic acid introduces octenyl succinic anhydride, the hydrogen bonding effect with agarose and sodium alginate is also strengthened, thereby constructing a second interconnected network and interspersing the first interconnected network to form a complex three-dimensional network structure. By enhancing the interaction between polymer chains, the elastic modulus is significantly improved; at the same time, the three-dimensional network structure also reduces the pore size, hinders the penetration of solvent molecules, slows down the swelling process and thus reduces the swelling rate; in addition, the uniform distribution of the modified components on the three-dimensional network can also effectively improve the cell survival rate. At the same time, the composite material also has suitable viscosity and degradation properties, which can meet application requirements.

[0027] (2) The modified carboxymethyl chitosan of the present invention introduces polyethylene glycol, which can form intermolecular forces such as hydrogen bonds with carboxymethyl chitosan. Through interaction, it helps to build a more stable and dense structure, thereby significantly improving the mechanical properties of the composite material. At the same time, polyethylene glycol can serve as a physical cross-linking point to improve resilience and durability through cross-linking, making it more resistant to external pressure and deformation. The combined effect improves the elastic modulus.

[0028] (3) The modified hyaluronic acid of the present invention uses octenyl succinic anhydride as a hydrophobic small molecule to modify the structure of hyaluronic acid. Octenyl succinic anhydride can form a hydrophobic region through the octenyl side chain, reducing the affinity for water molecules, thereby effectively reducing the swelling rate of the composite material; at the same time, the modification of octenyl succinic anhydride can change the surface charge distribution of hyaluronic acid, affect its interaction with cell surface receptors, and reduce the cytotoxicity of the material.

[0029] (4) In the agarose-modified sodium alginate of the present invention, agarose has good elasticity and strength, while sodium alginate has excellent flexibility. By compounding the two, the material has both good elasticity and flexibility, thereby optimizing the overall mechanical properties of the carboxymethyl chitosan composite material for the joint cavity and improving the elastic modulus. At the same time, agarose-sodium alginate will form mutually entangled filamentous structures and irregular depressions, which can better adhere to cells through the rough surface and filamentous tissue, which is beneficial to the growth and proliferation of cells and improves the cell survival rate.

[0030] (5) Chitosan in the titanium dioxide-doped chitosan of the present invention is a natural polysaccharide with good biocompatibility and degradability, and can support cell attachment, growth and differentiation; titanium dioxide has certain antioxidant properties, which can reduce the damage of oxidative stress to cells and is beneficial to maintaining the health of cells. The combination of the two can further optimize the surface properties of the material, increase its friendliness to cells, and improve the cell survival rate of the composite material. DETAILED DESCRIPTION

[0031] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0032] The sources of some components in the embodiments and comparative examples are as follows:

[0033] Carboxymethyl chitosan, product number 20121011, was purchased from Chengdu Kelong Chemical Reagent Factory;

[0034] Hyaluronic acid I, product number H909935, molecular weight 100,000-200,000, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0035] Hyaluronic acid II, product number H909937, molecular weight 400,000-800,000, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0036] Sodium alginate, CAS No. 9005-38-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0037] Chitosan, CAS No. 9012-76-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0038] Polyethylene glycol, product number P103728, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0039] Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0040] Calcium chloride, CAS No. 10043-52-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0041] Calcium bicarbonate, CAS No. 3983-19-5, purchased from Shanghai Huayuan Century Trading Co., Ltd.;

[0042] 2-Octenylsuccinic anhydride, CAS No. 42482-06-4, purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0043] Agarose, CAS No. 9012-36-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0044] Titanium dioxide, CAS No. 13463-67-7, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0045] Embodiment 1: This embodiment provides a method for preparing a carboxymethyl chitosan composite material for joint cavity, comprising the following steps:

[0046] Step S1: by weight, 10 parts of carboxymethyl chitosan and 6 parts of calcium salt (4 parts of calcium chloride and 2 parts of calcium bicarbonate) are added to 120 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L and mixed evenly to obtain a carboxymethyl chitosan solution; 30 parts of polyethylene glycol are added to 1120 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L and stirred evenly to obtain a polyethylene glycol solution; 20 parts of the carboxymethyl chitosan solution and 100 parts of the polyethylene glycol solution are mixed to perform a curing reaction, first stirred at 4° C. for 20 minutes, then reacted at 60° C. for 10 minutes, filtered, washed with water, and freeze-dried to obtain modified carboxymethyl chitosan;

[0047] Step S2: adding 30 parts of the modified carboxymethyl chitosan to 120 parts of a sodium hydroxide solution with a molar concentration of 0.2 mol / L to form a liquid A, and adding 8 parts of chitosan to 50 parts of an acetic acid solution with a molar concentration of 0.2 mol / L to form a liquid B;

[0048] Step S3: 120 parts of the liquid A and 50 parts of the liquid B are mixed, and then 10 parts of modified hyaluronic acid and 3 parts of agarose-modified sodium alginate are added and stirred evenly to obtain a carboxymethyl chitosan composite material for the joint cavity.

[0049] Preparation of the modified hyaluronic acid: by weight, 10 parts of hyaluronic acid I (article number H909935, molecular weight 100,000-200,000) are added to 100 parts of deionized water and mixed evenly, the pH is adjusted to 8.8, and then 4 parts of 2-octenylsuccinic anhydride are added, stirred overnight, dialyzed, and freeze-dried to obtain modified hyaluronic acid.

[0050] The preparation method of agarose-modified sodium alginate comprises: adding 8 parts of agarose to 120 parts of deionized water by weight, stirring evenly at 90° C., cooling to 75° C., adding 8 parts of sodium alginate and stirring for 4 hours to obtain a mixed solution; electrostatically spraying the mixed solution (liquid flow rate of 1.8 mL / h, voltage of 18 kV, receiving distance of 20 cm, time of 60 min), and freeze-drying to obtain agarose-modified sodium alginate.

[0051] The preparation of the titanium dioxide doped chitosan is as follows: by weight, 200 parts of deionized water and 100 parts of acetic acid are mixed evenly, then 4 parts of chitosan are added to fully dissolve, and then 3 parts of titanium dioxide are added and ultrasonically dispersed for 30 minutes, followed by stirring reaction (stirring speed is 200r / min, temperature is 50°C, time is 3h), after the stirring reaction is completed, 100 parts of sodium hydroxide solution with a molar concentration of 1mol / L is added, cooled to room temperature, filtered, washed with water, and dried to obtain titanium dioxide doped chitosan.

[0052] Embodiment 2: This embodiment provides a method for preparing a carboxymethyl chitosan composite material for a joint cavity, comprising the following steps:

[0053] Step S1: adding 6 parts of carboxymethyl chitosan and 4 parts of calcium salt (2 parts of calcium chloride and 2 parts of calcium bicarbonate) to 100 parts of sodium hydroxide solution with a molar concentration of 1 mol / L and mixing them evenly to obtain a carboxymethyl chitosan solution; adding 20 parts of polyethylene glycol to 100 parts of sodium hydroxide solution with a molar concentration of 1 mol / L and stirring them evenly to obtain a polyethylene glycol solution; mixing 10 parts of the carboxymethyl chitosan solution and 80 parts of the polyethylene glycol solution to perform a curing reaction, first stirring at 0° C. for 20 minutes, then reacting at a temperature of 50° C. for 20 minutes, filtering, washing with water, and freeze-drying to obtain modified carboxymethyl chitosan;

[0054] Step S2: adding 20 parts of the modified carboxymethyl chitosan to 100 parts of a sodium hydroxide solution with a molar concentration of 0.2 mol / L to form a liquid A, and adding 4 parts of chitosan to 40 parts of an acetic acid solution with a molar concentration of 0.2 mol / L to form a liquid B;

[0055] Step S3: 100 parts of the liquid A and 40 parts of the liquid B are mixed, and then 6 parts of modified hyaluronic acid and 1 part of agarose-modified sodium alginate are added and stirred evenly to obtain a carboxymethyl chitosan composite material for the joint cavity.

[0056] Preparation of the modified hyaluronic acid: by weight, 6 parts of hyaluronic acid I (article number H909935, molecular weight 100,000-200,000) are added to 80 parts of deionized water and mixed evenly, the pH is adjusted to 8.4, and then 2 parts of 2-octenylsuccinic anhydride are added, stirred overnight, dialyzed, and freeze-dried to obtain modified hyaluronic acid.

[0057] The preparation method of the agarose-modified sodium alginate comprises: adding 4 parts of agarose to 100 parts of deionized water by weight, stirring evenly at 80° C., cooling to 65° C., adding 4 parts of sodium alginate and stirring for 4 hours to obtain a mixed solution; electrostatically spraying the mixed solution (liquid flow rate of 1.2 mL / h, voltage of 14 kV, receiving distance of 16 cm, time of 80 min), and freeze-drying to obtain agarose-modified sodium alginate.

[0058] The preparation of the titanium dioxide doped chitosan is as follows: by weight, 180 parts of deionized water and 70 parts of acetic acid are mixed evenly, then 2 parts of chitosan are added to fully dissolve, and then 1 part of titanium dioxide is added for ultrasonic dispersion for 20 minutes and then stirred for reaction (stirring speed is 100 r / min, temperature is 40°C, time is 5 hours), after the stirring reaction is completed, 80 parts of sodium hydroxide solution with a molar concentration of 1 mol / L is added, cooled to room temperature, filtered, washed with water, and dried to obtain titanium dioxide doped chitosan.

[0059] Embodiment 3: This embodiment provides a method for preparing a carboxymethyl chitosan composite material for joint cavity, comprising the following steps:

[0060] Step S1: by weight, 8 parts of carboxymethyl chitosan and 5 parts of calcium salt (3 parts of calcium chloride and 2 parts of calcium bicarbonate) are added to 110 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L and mixed evenly to obtain a carboxymethyl chitosan solution; 25 parts of polyethylene glycol are added to 110 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L and stirred evenly to obtain a polyethylene glycol solution; 15 parts of the carboxymethyl chitosan solution and 90 parts of the polyethylene glycol solution are mixed to perform a curing reaction, first stirred at 2° C. for 15 minutes, then reacted at a temperature of 55° C. for 15 minutes, filtered, washed with water, and freeze-dried to obtain modified carboxymethyl chitosan;

[0061] Step S2: adding 25 parts of the modified carboxymethyl chitosan to 110 parts of a sodium hydroxide solution with a molar concentration of 0.2 mol / L to form a liquid A, and adding 6 parts of chitosan to 45 parts of an acetic acid solution with a molar concentration of 0.2 mol / L to form a liquid B;

[0062] Step S3: 110 parts of the liquid A and 45 parts of the liquid B are mixed, and then 8 parts of modified hyaluronic acid and 2 parts of agarose-modified sodium alginate are added and stirred evenly to obtain a carboxymethyl chitosan composite material for the joint cavity.

[0063] Preparation of the modified hyaluronic acid: by weight, 8 parts of hyaluronic acid I (article number H909935, molecular weight 100,000-200,000) are added to 90 parts of deionized water and mixed evenly, the pH is adjusted to 8.6, and then 3 parts of 2-octenylsuccinic anhydride are added, stirred overnight, dialyzed, and freeze-dried to obtain modified hyaluronic acid.

[0064] The preparation method of the agarose-modified sodium alginate comprises: adding 6 parts of agarose to 110 parts of deionized water by weight, stirring evenly at 85° C., cooling to 70° C., adding 6 parts of sodium alginate and stirring for 5 hours to obtain a mixed solution; electrostatically spraying the mixed solution (liquid flow rate of 1.6 mL / h, voltage of 16 kV, receiving distance of 18 cm, time of 70 minutes), and freeze-drying to obtain agarose-modified sodium alginate.

[0065] The preparation of the titanium dioxide doped chitosan is as follows: by weight, 190 parts of deionized water and 80 parts of acetic acid are mixed evenly, then 3 parts of chitosan are added to fully dissolve, and then 2 parts of titanium dioxide are added and ultrasonically dispersed for 25 minutes, followed by stirring reaction (stirring speed is 150r / min, temperature is 45°C, and time is 4h). After the stirring reaction is completed, 90 parts of sodium hydroxide solution with a molar concentration of 1mol / L is added, cooled to room temperature, filtered, washed with water, and dried to obtain titanium dioxide doped chitosan.

[0066] Comparative Example 1: This comparative example provides a method for preparing a carboxymethyl chitosan composite material for joint cavity. The difference from Example 1 is that commercially available carboxymethyl chitosan (item number 20121011) is used instead of modified carboxymethyl chitosan.

[0067] Comparative Example 2: This comparative example provides a method for preparing a carboxymethyl chitosan composite material for joint cavity. The difference from Example 1 is that the portion of calcium chloride in the calcium salt is changed to 5 portions, and the portion of calcium bicarbonate is changed to 1 portion.

[0068] Comparative Example 3: This comparative example provides a method for preparing a carboxymethyl chitosan composite material for joint cavity. The difference from Example 1 is that the portion of calcium chloride in the calcium salt is changed to 2 portions, and the portion of calcium bicarbonate is changed to 4 portions.

[0069] Comparative Example 4: This comparative example provides a method for preparing a carboxymethyl chitosan composite material for joint cavity, which differs from Example 1 in that hyaluronic acid I is used instead of modified hyaluronic acid.

[0070] Comparative Example 5: This comparative example provides a method for preparing a carboxymethyl chitosan composite material for joint cavity. The difference from Example 1 is that hyaluronic acid II is used instead of hyaluronic acid I to prepare the modified hyaluronic acid.

[0071] Comparative Example 6: This comparative example provides a method for preparing a carboxymethyl chitosan composite material for joint cavity. The difference from Example 1 is that commercially available sodium alginate (CAS No. 9005-38-3) is used instead of agarose-modified sodium alginate.

[0072] Comparative Example 7: This comparative example provides a method for preparing a carboxymethyl chitosan composite material for joint cavity. The difference from Example 1 is that commercially available chitosan (CAS No. 9012-76-4) is used instead of titanium dioxide to dope chitosan.

[0073] The performance of the carboxymethyl chitosan composite materials for joint cavity provided in the above embodiments and comparative examples was tested, and the testing method was as follows:

[0074] (1) Elastic modulus test: A cone-plate rotational rheometer (model DHR-1, Waters China Ltd.) was used to perform rheological property tests to determine the elastic modulus of the composite materials of the embodiments and comparative examples. During the tests, the stress-strain value was fixed at 10% and the frequency value was fixed at 2.5 Hz.

[0075] (2) Swelling rate test: The composite materials of the embodiment and the comparative example were completely immersed in a phosphate buffer solution with a pH of 7.4, and placed in an incubator at 37±1°C for 48 h. The test samples were taken out and the surface moisture was absorbed with filter paper and weighed. The swelling rate of the gel was calculated according to the following formula:

[0076] Swelling ratio = (mass of sample after swelling - mass of sample before swelling) / mass of sample before swelling × 100%.

[0077] (3) Cytotoxicity test: The test shall be conducted in accordance with the requirements of GB / T 16886.5-2017 Biological evaluation of medical devices Part 5: In vitro cytotoxicity test.

[0078] (4) Viscosity test: The composite materials of the examples and comparative examples were tested for viscosity using a rotational viscometer (model NDJ-5S, Shanghai Precision Instruments) at a test temperature of 25±1°C.

[0079] (5) Degradation performance test: 18 g of sodium acetate and 9.8 ml of glacial acetic acid were mixed, and then deionized water was added to dilute the mixture to 1000 mL of acetic acid-sodium acetate buffer. Then, lysozyme (with an activity unit of not less than 20,000 U / mg) was added to the buffer at a rate of 1 mg / mL to prepare an enzymatic solution. The composite materials of the examples and comparative examples were diluted with the enzymatic solution by multiple times, and degraded at 55°C for 48 h. The weight average molecular weight of the degradation solution was determined.

[0080] The above performance test data is shown in Table 1.

[0081] Table 1 Performance test results

[0082] Elastic modulus (Pa) Swelling rate (%) Cell survival rate (%) Viscosity (mPa.s) Weight average molecular weight after 48h degradation (g / mol) Example 1 125 3.8 95 321 25122 Example 2 121 4.4 92 315 25133 Example 3 123 4.1 93 318 25127 Comparative Example 1 98 12.6 79 302 25365 Comparative Example 2 109 8.2 86 309 25148 Comparative Example 3 111 7.9 87 311 25139 Comparative Example 4 101 11.9 81 305 25342 Comparative Example 5 108 8.4 86 310 25156 Comparative Example 6 99 12.2 80 303 25354 Comparative Example 7 102 11.7 82 306 25349

[0083] From the above content, it can be seen that the present invention selects carboxymethyl chitosan, hyaluronic acid, sodium alginate and chitosan with good biocompatibility as raw materials, and performs functional modification treatment respectively to prepare carboxymethyl chitosan composite materials for joint cavity (Examples 1~3), whose elastic modulus is 121~125Pa, swelling rate is 3.8~4.4%, cell survival rate is 92~95%, and the viscosity of the composite material is 315~321 mPa.s (not less than 300 mPa.s), and the weight average molecular weight after 48h degradation is 25122~25133 g / mol (not more than 26000g / mol), which can meet the application requirements.

[0084] Compared with Example 1, commercially available carboxymethyl chitosan (Article No. 20121011) was used to replace the modified carboxymethyl chitosan, and the elastic modulus was reduced, the swelling rate was increased, and the cell survival rate was reduced (Comparative Example 1); Compared with Example 1, the number of calcium chloride in the calcium salt was changed to 5 parts, and the number of calcium bicarbonate was changed to 1 part. Due to the small amount of calcium bicarbonate, the prepared modified carboxymethyl chitosan had a poor effect, the elastic modulus was reduced, the swelling rate was increased, and the cell survival rate was reduced (Comparative Example 2); Compared with Example 1, the number of calcium chloride in the calcium salt was changed to 2 parts, and the number of calcium bicarbonate was changed to 4 parts. Due to the excessive amount of calcium bicarbonate, the prepared modified carboxymethyl chitosan had a poor effect, the elastic modulus was reduced, the swelling rate was increased, and the cell survival rate was reduced (Comparative Example 3); Compared with Example 1, hyaluronic acid was used Compared with Example 1, when hyaluronic acid II was used to replace hyaluronic acid I for the preparation of modified hyaluronic acid, the elastic modulus was reduced, the swelling rate was increased, and the cell survival rate was reduced (Comparative Example 4); compared with Example 1, hyaluronic acid II was used to replace hyaluronic acid I. Since the molecular weight of hyaluronic acid II was too large, the modification effect was not good, the elastic modulus was reduced, the swelling rate was increased, and the cell survival rate was reduced (Comparative Example 5); compared with Example 1, commercially available sodium alginate (CAS No. 9005-38-3) was used to replace agarose-modified sodium alginate, the elastic modulus was reduced, the swelling rate was increased, and the cell survival rate was reduced (Comparative Example 6); compared with Example 1, commercially available chitosan (CAS No. 9012-76-4) was used to replace titanium dioxide-doped chitosan, the elastic modulus was reduced, the swelling rate was increased, and the cell survival rate was reduced (Comparative Example 7).

[0085] In summary, the present invention selects carboxymethyl chitosan, hyaluronic acid, sodium alginate and chitosan with good biocompatibility as raw materials, and performs functional modification treatments respectively to prepare a carboxymethyl chitosan composite material for the joint cavity. Through the synergistic effect of each component, the elastic modulus of the composite material is effectively improved, the swelling rate is reduced, and a good cell survival rate is ensured. At the same time, the composite material also has suitable viscosity and degradation performance, which can meet application requirements.

Claims

1. A method for preparing a carboxymethyl chitosan composite material for joint cavity, characterized in that: The following steps are involved: Step S1: adding 6 to 10 parts of carboxymethyl chitosan and 4 to 6 parts of calcium salt to 100 to 120 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L and mixing them uniformly to obtain a carboxymethyl chitosan solution; adding 20 to 30 parts of polyethylene glycol to 100 to 120 parts of a sodium hydroxide solution with a molar concentration of 1 mol / L and stirring them uniformly to obtain a polyethylene glycol solution; mixing 10 to 20 parts of the carboxymethyl chitosan solution and 80 to 100 parts of the polyethylene glycol solution to perform a curing reaction, filtering, washing with water, and freeze-drying to obtain modified carboxymethyl chitosan; Step S2: adding 20 to 30 parts of the modified carboxymethyl chitosan to 100 to 120 parts of a sodium hydroxide solution with a molar concentration of 0.2 mol / L to form a liquid A, and adding 4 to 8 parts of titanium dioxide-doped chitosan to 40 to 50 parts of an acetic acid solution with a molar concentration of 0.2 mol / L to form a liquid B; Step S3: mixing 100-120 parts of the liquid A and 40-50 parts of the liquid B, and then adding 6-10 parts of modified hyaluronic acid and 1-3 parts of agarose-modified sodium alginate and stirring evenly to obtain a carboxymethyl chitosan composite material for joint cavity; The calcium salt is calcium chloride and calcium bicarbonate; the mass ratio of calcium chloride to calcium bicarbonate is (1-2):1; The preparation method of the modified hyaluronic acid comprises: adding 6 to 10 parts of hyaluronic acid to 80 to 100 parts of deionized water by weight, mixing evenly, adjusting the pH to 8.4 to 8.8, then adding 2 to 4 parts of 2-octenyl succinic anhydride, stirring overnight, dialyzing, and freeze-drying to obtain the modified hyaluronic acid; The preparation method of agarose-modified sodium alginate comprises: adding 4 to 8 parts of agarose to 100 to 120 parts of deionized water by weight, stirring evenly at 80 to 90° C., cooling to 65 to 75° C., adding 4 to 8 parts of sodium alginate and stirring for 4 to 6 hours to obtain a mixed solution; electrostatically spraying the mixed solution, freeze-drying, and obtaining agarose-modified sodium alginate; The preparation method of titanium dioxide doped chitosan comprises: in parts by weight, 180-200 parts of deionized water and 70-100 parts of acetic acid are uniformly mixed, then 2-4 parts of chitosan are added to fully dissolve, and then 1-3 parts of titanium dioxide are added to ultrasonically disperse for 20-30 minutes and then stirred to react, after the stirring reaction is completed, 80-100 parts of sodium hydroxide solution with a molar concentration of 1 mol / L are added, cooled to room temperature, filtered, washed with water, and dried to obtain titanium dioxide doped chitosan.

2. The method for preparing a carboxymethyl chitosan composite material for joint cavity according to claim 1, characterized in that: The curing reaction conditions include: stirring at 0-4° C. for 10-20 min, and then reacting at 50-60° C. for 10-20 min.

3. The method for preparing a carboxymethyl chitosan composite material for joint cavity according to claim 1, characterized in that: The conditions of the electrostatic spray include: a liquid flow rate of 1.2-1.8 mL / h, a voltage of 14-18 kV, a receiving distance of 16-20 cm, and a time of 60-80 min.

4. The method for preparing a carboxymethyl chitosan composite material for joint cavity according to claim 1, characterized in that: The stirring reaction conditions include: stirring speed of 100-200 r / min, temperature of 40-50° C., and time of 3-5 h.

5. A carboxymethyl chitosan composite material for joint cavity, characterized in that: Prepared according to the method according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • A joint injection gel and its preparation method

    CN115671405B

  • Preparation method of multiple cross-linked polysaccharide injectable hydrogel

    CN104479150A

  • Articular cavity injection gel and preparation method thereof

    CN115671405A